POSTULATING THEORY SYNTHESIZATION FOR STRATEGIC ALLIANCE AND COMPETITIVE ADVANTAGE SUCCESS IN NIGERIA - Ojukwu, Henry Sonna (Milestone: Journal of Strategic Management, 2024)
Irrespective of country and economy, organizations around the globe are constantly scanning for ways to enhance their competitive position for sustained industry performance amidst heightened competition. Rather than competing against each other, these firms view themselves as strategic partners for long-term industry relationships. To this end, the study analyzed how theoretical Synthesization would greatly influence the positional standing of aligning firms. To achieve the study intent, the scoping review approach was employed. Study materials were mainly journal articles sourced from academic search engines and institutional databases. The study clearly states that regarding strategic alliance and competitive advantage, the essence of possessing rare, uncopiable, and non-substitutability organizational resources should be for inter-organizational purposes rather than individualist exploitation.